Catheter Injectable Multifunctional Biomaterial for the Treatment of Infected Enterocutaneous Fistulas - Jinjoo Kim; Zefu Zhang; Hassan Albadawi; Hyeongseop Keum; Joseph L. Mayer; Erin H. Graf; Rahmi Oklu (Advanced Science)
Abstract Enterocutaneous fistulas (ECF) are challenging to treat contributing to high morbidity and high mortality rates, significantly impacting the quality of life of the patients. Its susceptibility to antibiotic‐resistant infections often leads to chronic inflammation, complicating treatment with conventional methods. Here, 18NC75‐10P‐1IL is reported, which is a multi‐functional shear‐thinning hydrogel comprised of gelatin and nanosilicates for injectability, an ionic liquid for bactericidal effects, and platelet rich fibrin fraction for pro‐healing properties; this biomaterial is engineered for the treatment of ECFs. Through rigorous testing, the mechanical properties of 18NC75‐10P‐1IL were tailored for catheter injection to achieve durable occlusion of fistulous tracts under external pressures simulating clinical scenarios. 18NC75‐10P‐1IL demonstrated pro‐healing effects and anti‐microbial activity against highly resistant patient‐derived bacteria known to be associated with ECF. Subcutaneous implantation and anorectal fistula models confirmed its biocompatibility, pro‐healing, anti‐inflammatory, and anti‐microbial properties compared to control materials, suggesting promising potential for clinical translation in the treatment of human ECFs.